Potassium phosphite on the control of downy mildew of grapevine and physicochemical characteristics of Merlot grapes - Pereira, Vanessa Foresti; Resende, Mário Lúcio Vilela de; Ribeiro Júnior, Pedro Martins; Regina, Murillo de Albuquerque; Mota, Renata Vieira da; Vitorino, Luiz Rodolpho Rodrigues (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of increasing doses of two formulations of potassium phosphite, on the severity of downy mildew of grapevine, yield and on physicochemical characteristics of Merlot grapes. Two formulations of potassium phosphite (Phi A and B) were evaluated at the doses 0, 1.2, 2.5, 3.7 and 5.0 g L-1 of P2O5, in comparison with a foliar fertilizer and fungicides, during the 2009/2010 and 2010/2011 crop seasons. There was a linear effect of phosphite doses on the reduction of the downy mildew severity, in the two crop seasons. The Phi A highest dose provided an average control of 60.5%, and Phi B, 57.7%, similar to the control by the fungicides (64.3%) and fertilizer (53.3%). In the first harvest, Phi B provided a greater productivity, while, in the second, it did not differ from the treatment with fungicides. Treatments only affected soluble solids, pH and total acidity of the grape must in the second season. Phi B and fungicides provided the highest levels of total soluble phenolic compounds at the grape peel, however, had no effect on the levels of anthocyanins. Potassium phosphite application increases total soluble solids and pH, reduces total titratable acidity of the berries, does not affect anthocyanin contents, and it is an effective alternative for the control of downy mildew, with response similar to that of fungicides.